Pengaruh Kualitas Pelayanan, Citra Merek, Nilai Nasabah Dan Motivasi Anggota Terhadap Loyalitas Anggota Di Koperasi Serba Usaha Rantauprapat - Parwati, Kintan (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the effect of service quality, brand image, customer value and motivation of members of the loyalty of members in KSU Rantauprapat, either partially or simultaneously. Data collection using interview techniques, questionnaires and literature studies. Execution of data analysis methods using the help of software SPSS 22.0 for windows. This study used a sample of 100 people in the sampling method is simple random side. simple random aside is a random sampling system and provides equal opportunities for every member of the population to express their opinions. Hypothesis testing results persial (t test) showed that the quality of Service(X1) significant positive effect on member loyalty (Y) where the value of thitung (1.795)< ttable (1.985) and the probability of 0.076> 0.05. Brand image (X2) positive and significant effect on member loyalty (Y), where the value of thitung ( 0.690) < ttable (1.985) and probability 0.492> 0.05. Customer value (X3) significant positive effect on member loyalty (Y), where the value of the count (4.063) > ttable (1.985) and the probability of 0.000 < 0.05.Member motivation (X4) significant positive effect on member loyalty (Y), where the value of the count (3.332) > ttable ( 1.985) and the probability of 0.001 < 0.05. The results of the study based on the simultaneous test (F test) showed that simultaneously (simultaneously) variable quality of Service (X1), brand image (X2), customer value (X3), and member motivation (X4) simultaneously positive and significant effect on member loyalty (Y) KSU Riama Rantauprapat, with a significant level of value Fcount (9.611) > Ftable (2.47) and the probability of 0.000 < 0.05. Based on the results of the coefficient determination test Adjusted R Squareindicates that the quality of Service (X1), brand image (X2), Customer Value (X3), and motivation of members (X4) can affect the loyalty of members (Y) at KSU Riama Rantauprapat by 25.8%.While the remaining 74.2% of member loyalty is influenced by other factors that are not discussed in this study.Â